Abrasion-resistant and sound-dampening engineering plastic composition, method for producing the same, and applications

JP2026536549APending Publication Date: 2026-10-30FINE BLEND POLYMER SHANGHAI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2026523278
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-06-28
Filing Date
2024-08-23
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

【0020】 従来技術と比較して、本発明は以下の有益な効果を有する。本発明は、ポリオレフィン-スチレングラフト共重合体または反応性官能基で変性されたポリオレフィン-スチレングラフト共重合体の少なくとも1種を耐摩耗·制音助剤として添加することにより、当該グラフトポリマーのスチレンまたは反応性官能基を有するスチレン構造がエンジニアリングプラスチックのマトリックスと末端基反応、水素結合または極性構造の類似等の方法により効果的に結合し、主鎖のポリオレフィン構造が改質されたエンジニアリングプラスチックの表面に耐摩耗層を形成し、かつエンジニアリングプラスチックのマトリックスと層間剥離を起こさないため、持続的な耐摩耗効果が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026536549000001_ABST
    Figure 2026536549000001_ABST
Patent Text Reader

Abstract

This invention provides an environmentally friendly abrasion-resistant and sound-dampening engineering plastic composition, its manufacturing method, and its applications. [Solution] This composition comprises the following components: thermoplastic resin, reinforcing filler, abrasion-resistant and sound-dampening agent, abrasion-resistant additive, and processing aid. The abrasion-resistant and sound-dampening agent comprises at least one polyolefin-styrene graft copolymer or polyolefin-styrene graft copolymer modified with reactive functional groups. The abrasion-resistant additive is one or more selected from UHMWPE, polysiloxane, molybdenum disulfide, graphite, and modified fatty acid esters. The reinforcing filler comprises at least one glass fiber, carbon fiber, and inorganic mineral. By using the abrasion-resistant and sound-dampening agent and the abrasion-resistant additive in combination, the abrasion resistance and sound dampening properties of the modified engineering plastic can be significantly improved, while being environmentally friendly and maintaining the mechanical properties of the modified material.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention belongs to the field of polymer material modification technology, and relates to an eco-friendly wear-resistant and noise-damping thermoplastic engineering plastic and a preparation method thereof. BACKGROUND ART

[0002] Wear resistance is one of the main mechanical properties of thermoplastic engineering plastics, and wear-resistant engineering plastics can be used in the manufacture of various mechanical parts such as gears, pulleys, sliders and rollers, with extremely wide industrial applications.

[0003] There are many types of anti-wear agents for polymer materials, including molybdenum disulfide (MoS₂), graphite, carbon fiber, polytetrafluoroethylene (PTFE), silicone (silicone oil), ultra-high molecular weight polyethylene (UHMWPE) and the like. However, each wear-resistant and low-friction component has its own characteristics. For example, PTFE has high versatility and an extremely low friction coefficient. The effect of silicone is generally enhanced when used in combination with PTFE. Graphite is more suitable for water environments, and has low adhesion to the base material under dry conditions, making it easy to fall off. Molybdenum disulfide is widely used as a solid lubricant, but its friction coefficient is not sufficiently low. However, a comprehensive analysis of many usage scenarios shows that the most representative anti-wear additive is still PTFE. For example, the wear-resistant nylon composition described in Patent Document 1 reduces the transmittance of the nylon composition by selecting the reaction between an epoxy resin having a specific epoxy value and the end groups of PA66, so as to suppress the penetration of the lubricating grease component, and effectively inhibit the decomposition of PA66 in combination with an antioxidant. By combining PA66 resin and PTFE, the lubricating and wear-resistant properties of PTFE are fully exerted, so that the nylon composition has excellent wear resistance even under the action of high-temperature lubricating grease.

[0004] PTFE is used as an abrasion resistant agent, but it also has many drawbacks. Firstly, PTFE is added in large quantities to plastic formulations, and if the content is low, the abrasion resistant effect of the modified material is not clear. Secondly, PTFE is a completely nonpolar material, has low compatibility with most thermoplastic engineering plastics, is difficult to extrude and granulate, has significant surface defects, and its mechanical properties are greatly reduced. Thirdly, PTFE is a type of perpolyfluoroalkyl substance (PFAS), and fluorine-containing polymers have extremely high chemical stability, and once released into the environment, they persist for a long time and cause environmental damage. New EU regulatory proposals require regulation of all PFAS, with the aim of banning the use and manufacture of all PFAS in the EU, and PTFE is included in this. Furthermore, the manufacturing process of PTFE also uses substances such as PFOA (perfluorooctanoic acid and its salts and related compounds) and PFOS (perfluorooctanesulfonic acid compounds), which the EU has already banned. Therefore, from an environmental protection standpoint, PTFE is no longer an appropriate choice.

[0005] Thermoplastic engineering plastics are widely used in the automotive and home appliance sectors due to their many advantages, but they also present some problems. For example, noise problems in home appliances and automotive products are currently a major concern for both industries. Many home appliances generate heat or cool down during operation, causing thermal expansion and contraction between different parts, resulting in a "creaking" noise, which frequently occurs in air conditioning products. In automotive products, vibrations during driving and external forces pressing on parts cause friction between parts, resulting in a "squeaking" noise. Such noises are caused by friction between plastic parts, or between plastic parts and leather or metal parts. Therefore, solving the noise reduction problem of thermoplastic materials is also a key issue for the industry. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Chinese Patent Application Publication No. 116478534 [Overview of the project] [Problems that the invention aims to solve]

[0007] This invention provides an environmentally friendly wear-resistant and sound-dampening engineering plastic and a method for producing the same. By employing a novel formulation and a technology that combines an environmentally friendly wear-resistant and sound-dampening additive with a wear-resistant additive, it is possible not only to improve the friction properties of some engineering plastics but also to perform sound-dampening and noise-reducing functions in some thermoplastic resins, showing a particularly significant improvement effect on modified engineering plastics applied in fields such as automobiles and home appliances. [Means for solving the problem]

[0008] The object of the present invention can be achieved by the following technical means. The abrasion-resistant and sound-dampening engineering plastic composition comprises the following components: thermoplastic resin, abrasion-resistant and sound-dampening additive, abrasion-resistant additive, and processing aid; it may also contain reinforcing fillers.

[0009] In the present invention, the weight ratio of thermoplastic resin, reinforcing filler, wear-resistant / sound-dampening agent, wear-resistant agent, and processing aid is 100:(0~60):(1~20):(0.1~10):(0.1~20), and preferably, the weight ratio of thermoplastic resin, reinforcing filler, wear-resistant / sound-dampening agent, wear-resistant agent, and processing aid is 100:(0~60):(2~15):(0.5~5):(0.1~20).

[0010] The present invention discloses a method for producing the above-mentioned abrasion-resistant and sound-dampening engineering plastic composition, which is manufactured from a thermoplastic resin, a reinforcing filler, an abrasion-resistant and sound-dampening aid, an abrasion-resistant aid, and a processing aid. Specifically, these raw materials are manufactured into the above-mentioned abrasion-resistant and sound-dampening engineering plastic composition by an extrusion process.

[0011] In the present invention, the wear-resistant and sound-dampening agent is at least one selected from polyolefin-styrene graft copolymers or polyolefin-styrene graft copolymers modified with reactive functional groups. Here, the polyolefin-styrene graft copolymer is obtained by grafting a styrene-based polymer onto a substituted or unsubstituted polyolefin molecular main chain. The polyolefin-styrene graft copolymer modified with reactive functional groups is a graft copolymer in which reactive functional groups such as acid anhydride, epoxy, acrylic, or carboxylic acid are introduced into a polyolefin-styrene graft copolymer, and the reactive functional group is one or more selected from the group consisting of acrylic acid, methacrylic acid, maleic anhydride, fumaric acid, dibutyl maleate, citric acid, itaconic acid, and glycidyl methacrylate groups. The polyolefin is at least one selected from the group consisting of low-density polyethylene, high-density polyethylene, linear low-density polyethylene, ultra-high molecular weight polyethylene, ethylene-α-olefin copolymers such as ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, and ethylene-octene copolymer, ethylene-vinyl acetate copolymer, and ethylene-acrylic acid ester copolymer. The styrene polymer is one selected from the group consisting of styrene, alkyl-substituted styrene having 1 to 10 carbon atoms, and halogen-substituted styrene.

[0012] In the present invention, the polyolefin-styrene graft copolymer modified with a reactive functional group is produced by the reaction of a polyolefin with a styrene polymer containing a reactive functional group.

[0013] Preferably, in the polyolefin-styrene graft copolymer or polyolefin-styrene graft copolymer modified with a reactive functional group, the weight ratio of polyolefin is 50-95%, and correspondingly, the weight ratio of the styrene polymer or styrene polymer having a reactive functional group is 5-50%.

[0014] In the present invention, the thermoplastic resin is one or more selected from the group consisting of nylon, polyacetal, polyphenylene sulfide, polycarbonate, or alloys thereof. Preferably, the nylon is one or more aliphatic nylon, aromatic nylon, long-chain nylon, or copolymer nylon, and the alloy is one of the alloys such as PC / ABS, PC / ASA, PC / PBT, or PC / PET.

[0015] In the present invention, the reinforcing filler is one or more selected from the group consisting of glass fibers, carbon fibers, or other inorganic minerals.

[0016] In the present invention, the processing aid includes at least one selected from the group consisting of antioxidants, lubricants, antibacterial agents, nucleating agents, antistatic agents, ultraviolet absorbers, colorants, compatibilizers, coupling agents, and impact modifiers.

[0017] In the present invention, the wear-resistant additive is one or more selected from the group consisting of UHMWPE, polysiloxane, molybdenum disulfide, graphite, and modified fatty acid esters.

[0018] This invention discloses the use of the above-mentioned wear-resistant and sound-dampening engineering plastic composition in the manufacture of wear-resistant materials.

[0019] This invention discloses wear-resistant and sound-dampening plastics, which are manufactured from the above-mentioned wear-resistant and sound-dampening engineering plastic compositions. Furthermore, it discloses the use of the above-mentioned wear-resistant and sound-dampening plastics in the manufacture of polymer wear-resistant products. [Effects of the Invention]

[0020] Compared with the prior art, the present invention has the following beneficial effects. By adding at least one of a polyolefin-styrene graft copolymer or a polyolefin-styrene graft copolymer modified with a reactive functional group as an abrasion-resistant and noise-reducing auxiliary agent, the styrene or the styrene structure with a reactive functional group of the graft polymer can effectively bond with the engineering plastic matrix through methods such as end group reaction, hydrogen bonding or similarity of polar structures, the polyolefin structure of the main chain forms an abrasion-resistant layer on the surface of the modified engineering plastic, and no delamination occurs with the engineering plastic matrix, so that a lasting abrasion-resistant effect can be obtained.

[0021] The present invention further improves the abrasion resistance and noise reduction performance of engineering plastics by using a composite of the polyolefin-styrene graft copolymer or the polyolefin-styrene graft copolymer modified with a reactive functional group and relatively environmentally friendly abrasion-resistant auxiliary agents such as UHMWPE, silicone, molybdenum disulfide, and modified fatty acid esters.

[0022] The anti-wear agent composed of the polyolefin-styrene graft copolymer or the polyolefin-styrene graft copolymer modified with a reactive functional group used in the present invention is a substitute for conventional PTFE with environmental risks, and is a technical means suitable for application in green industries. [Brief Description of the Drawings]

[0023] [Figure 1] This is an infrared spectrogram of the ethylene-octene-styrene-glycidyl methacrylate graft copolymer in Example 1. The vicinity of 1730 cm⁻¹ is the carbonyl stretching vibration absorption peak in glycidyl methacrylate, 1492 cm⁻¹ and 1452 cm⁻¹ are the skeleton vibration absorption peaks of the aromatic ring, 1378 cm⁻¹ and 719 cm⁻¹ are the characteristic peaks of ethylene-octene, and 698 cm⁻¹ represents the C-H out-of-plane bending vibration on the aromatic ring. [Figure 2]These are friction performance test results, wherein (a), (b) and (c) respectively show a comparison of wear scar widths after the friction test of the friction test pieces in Example 2, Comparative Example 2 and Comparative Example 2'. Detailed Description of the Embodiments

[0024] In the present invention, the raw materials are manufactured into the above wear-resistant and noise-damping engineering plastic composition through an extrusion process. Specifically, the method for producing the wear-resistant and noise-damping engineering plastic composition includes the following steps.

[0025] (1) A thermoplastic resin, a wear-resistant and noise-damping auxiliary agent, a wear-resistant auxiliary agent and a processing auxiliary agent are uniformly mixed at a predetermined ratio to obtain a premix, which is then fed through the main feed port of an extruder.

[0026] (2) After a reinforcing filler (if present) is metered at a predetermined ratio, it is fed into the extruder through the side feed port of the extruder.

[0027] (3) After the above materials are melt-kneaded and extruded, the wear-resistant and noise-damping engineering plastic composition is obtained by a cutting granulator.

[0028] As an example, the L / D ratio of the twin-screw extruder used is (36 to 52):1, the processing temperature is 150 to 320°C, and the rotation speed is 250 to 600 rpm.

[0029] Hereinafter, the present invention will be described in detail with reference to specific examples. The following examples help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It is pointed out that those of ordinary skill in the art can make various modifications and improvements without departing from the concept of the present invention, all of which fall within the protection scope of the present invention. All raw materials used in the present invention are existing products, and the specific manufacturing operations and performance tests are carried out by conventional methods.

[0030] The specific manufacturing operations for polyolefin-styrene graft copolymers or polyolefin-styrene graft copolymers modified with reactive functional groups are conventional methods. As an example, the manufacturing method for polyolefin-styrene graft copolymers modified with reactive functional groups in the present invention is as follows: The corresponding functional polymer is synthesized by a two-step method. First step: A styrene-based polymer containing reactive functional groups is produced by polymerization methods such as bulk polymerization, solution polymerization, or suspension polymerization. Second step: Various polyolefins are subjected to ultrasonic treatment / catalysis and reacted with the reaction product from the first step by extrusion to obtain the final target product.

[0031] As an example, the specific manufacturing method for glycidyl methacrylate graft copolymer is as follows:

[0032] (1) Mix styrene monomer, glycidyl methacrylate monomer, oil-soluble initiator, dispersant, co-dispersant, molecular weight modifier, and deionized water in a reaction vessel in weight ratio, raise the temperature to 75-85°C and react for 4-6 hours with stirring, then raise the temperature to 85-90°C and age for 1-3 hours. After completion, transfer to a storage tank, filter the obtained material, wash with deionized water, dry until constant weight is reached, and then sieve to obtain the intermediate.

[0033] (2) The polyolefin, the above intermediate, the imidazole catalyst, the reactive monomer, and the processing aid are weighed in proportion to each other and mixed uniformly. The mixture is then fed into a twin-screw extruder, where it undergoes melt mixing, extrusion reaction, and defoliation before being granulated and dried to obtain the desired functional polymer. The L / D ratio of the twin-screw extruder is 44-56:1, the extrusion temperature is 160-240°C, and the screw rotation speed is 200-400 rpm.

[0034] By following the method described above, polyolefin-styrene graft copolymers modified with different reactive functional groups can be obtained by replacing the styrene monomer with another styrene monomer, or the glycidyl methacrylate monomer with another reactive functional group monomer. [Examples]

[0035] The specific method for producing the ethylene-octene-styrene-glycidyl methacrylate graft copolymer is as follows:

[0036] (1) Mix 38 parts by weight of styrene monomer, 2 parts of glycidyl methacrylate monomer, 0.2 parts by weight of oil-soluble initiator azobisisobutyronitrile, 0.4 parts by weight of dispersant polyvinyl alcohol, 0.02 parts by weight of co-dispersant sodium dodecyl sulfate, 0.2 parts by weight of molecular weight of molecular weight dodecyl mercaptan, and deionized water in a total monomer weight ratio of 2:1 in a reaction vessel, raise the temperature to 80°C and react for 5 hours with stirring, then raise the temperature to 90°C and age for 2 hours. After completion, transfer to a storage tank, filter the obtained material, wash three times with deionized water, dry at 80°C until constant weight is reached, and then sieve to obtain the intermediate.

[0037] (2) 60 parts by weight of ethylene-octene copolymer (POE Engage 8200), 40 parts of the above intermediate, 0.2 parts of imidazole catalyst (2-methylimidazole), 0.5 parts of reactive monomer acrylic acid, and processing aids (0.2 parts of antioxidant 168, 0.2 parts of 1010, and 0.3 parts of lubricant EBS) are weighed and uniformly mixed, then fed into a twin-screw extruder, melt-mixed, extruded, and devolatilized to obtain the desired functional polymer, ethylene-octene-styrene-glycidyl methacrylate graft copolymer. Refer to Figure 1 for infrared spectroscopy testing of the product. The L / D ratio of the twin-screw extruder is 50:1, the extrusion temperature is 160-240°C, and the screw rotation speed is 300 rpm.

[0038] A wear-resistant and sound-dampening engineering plastic composition is prepared from the following parts by weight: 100 parts PPS resin (Zhejiang Xinhacheng), 45 parts glass fiber (584), 5 parts ethylene-octene-styrene-glycidyl methacrylate graft copolymer as a wear-resistant and sound-dampening aid, 3 parts graphite as a wear-resistant aid, and 0.5 parts antioxidant 1790.

[0039] After uniformly mixing the above raw materials, they are fed into an extruder with an L / D ratio of 40:1. Glass fibers are fed in through the side feed port, and the mixture is extruded and granulated at a processing temperature of 280-320°C and a rotation speed of 250 rpm to obtain a sample. After drying the pellets, test specimens are prepared by injection molding using a conventional method and subjected to testing. [Examples]

[0040] A wear-resistant and sound-dampening engineering plastic composition is prepared from the following parts by weight: 100 parts PA66 (EPR27), 30 parts glass fiber (560A), 10 parts linear low-density polyethylene-styrene graft copolymer (BP-231, Jiayirong Polymer (Shanghai) Co., Ltd.) as a wear-resistant and sound-dampening additive, 0.5 parts silicone masterbatch (GENIOPLAST Pellets S, Wacker Chemie) as a wear-resistant additive, 0.2 parts antioxidant 1098, and 0.2 parts antioxidant 168. The linear low-density polyethylene-styrene graft copolymer is prepared from 70 parts linear low-density polyethylene and 30 parts styrene.

[0041] After uniformly mixing the above raw materials, they are fed into an extruder with an L / D ratio of 40:1. Glass fibers are fed in through the side feed port, and the mixture is extruded and granulated at a processing temperature of 250-270°C and a rotation speed of 300 rpm to obtain a sample. After drying the pellets, test specimens are prepared by injection molding using a conventional method and subjected to testing. [Examples]

[0042] A wear-resistant and sound-dampening engineering plastic composition is manufactured from the following parts by weight: 100 parts PA6 (1013B, Ube Corporation, Japan), 60 parts carbon fiber (HTC413), 15 parts low-density polyethylene-styrene-maleic anhydride graft copolymer as a wear-resistant and sound-dampening aid, 5 parts molybdenum disulfide as a wear-resistant aid, 0.2 parts antioxidant 1098, 0.2 parts antioxidant 168, 8 parts impact modifier (FB521A, Jiayirong Polymer (Shanghai) Co., Ltd.), and 0.4 parts lubricant (erucic acid amide). The low-density polyethylene-styrene-maleic anhydride graft copolymer is produced from 90 parts linear low-density polyethylene, 9.5 parts styrene, and 0.5 parts maleic anhydride. The production method is the same as in Example 1, but the ethylene-octene copolymer is replaced with low-density polyethylene (Tsubameyama Petrochemical 1150A), and the glycidyl methacrylate monomer is replaced with maleic anhydride.

[0043] After uniformly mixing the above raw materials, they are fed into an extruder with an L / D ratio of 44:1. Carbon fibers are fed in through the side feed port, and the mixture is extruded and granulated at a processing temperature of 230-250°C and a rotation speed of 400 rpm to obtain a sample. After drying the pellets, test specimens are prepared by injection molding using a conventional method and subjected to testing. [Examples]

[0044] A wear-resistant and sound-dampening engineering plastic composition is prepared from the following parts by weight: 100 parts POM (F20-03, KEP Korea), 2 parts ethylene-vinyl acetate-styrene-acrylic acid graft copolymer as a wear-resistant and sound-dampening additive, 2 parts UHMWPE (T0604F, Sino-Petrochemical) as a wear-resistant additive, 0.2 parts antioxidant 245, and 1 part carbon black masterbatch (Cabot UN2014). The ethylene-vinyl acetate-styrene-acrylic acid graft copolymer is prepared from 50 parts ethylene-vinyl acetate copolymer, 49 parts styrene, and 1 part acrylic acid. The manufacturing method is the same as in Example 1, but the ethylene-octene copolymer is replaced with ethylene-vinyl acetate copolymer (Yansan Petrochemical EVA V5110J), and the glycidyl methacrylate monomer is replaced with acrylic acid.

[0045] After uniformly mixing the above raw materials, they are fed into an extruder with an L / D ratio of 36:1 and extruded at a processing temperature of 150-170°C and a rotation speed of 250 rpm to obtain a sample. After drying the pellets, test specimens are prepared by injection molding using a conventional method and subjected to testing. [Examples]

[0046] A wear-resistant and sound-dampening engineering plastic composition is prepared from the following parts by weight: 100 parts PC (1100, Lotte Chemical), a composite of 5 parts ultra-high molecular weight polyethylene-styrene copolymer (BP-2301, Jiayirong Polymer (Shanghai) Co., Ltd.) and 5 parts low-density polyethylene-styrene-glycidyl methacrylate graft copolymer as an wear-resistant and sound-dampening aid, 1 part high-purity fatty acid ester (M-B96R, Nippon Oil & Fats) as an wear-resistant aid, and 0.3 parts antioxidant 923. The ultra-high molecular weight polyethylene-styrene copolymer is prepared from 60 parts ultra-high molecular weight polyethylene and 40 parts styrene. The low-density polyethylene-styrene-glycidyl methacrylate graft copolymer is prepared from 75 parts low-density polyethylene (Yanshan Petrochemical 1150A), 20 parts styrene, and 5 parts glycidyl methacrylate, and its manufacturing method is the same as in Example 1, except that the ethylene-octene copolymer in the second step is replaced with low-density polyethylene.

[0047] After uniformly mixing the above raw materials, they are fed into an extruder with an L / D ratio of 52:1 and extruded at a processing temperature of 250-280°C and a rotation speed of 600 rpm to obtain a sample. After drying the pellets, test specimens are prepared by injection molding using a conventional method and subjected to testing. [Examples]

[0048] A wear-resistant and sound-dampening engineering plastic composition is manufactured from the following parts by weight: 70 parts PC (1220, Lotte Chemical), 30 parts ABS (8434, Takahashi Petrochemical), a composite of 2 parts ethylene-methyl acrylate-styrene-glycidyl methacrylate graft copolymer and 3 parts low-density polyethylene-styrene graft copolymer (BP-2305, Jiayirong Polymer (Shanghai) Co., Ltd.) as a wear-resistant and sound-dampening aid, 1 part silicone (MB50-001) as a wear-resistant aid, 0.3 parts antioxidant 1076, 0.2 parts antioxidant 168, 1 part compatibilizer (SAG-002, Jiayirong Polymer (Shanghai) Co., Ltd.), and 4 parts impact modifier (SBG-715, Jiayirong Polymer (Shanghai) Co., Ltd.). The ethylene-methyl acrylate-styrene-glycidyl methacrylate graft copolymer is produced from 50 parts of ethylene-methyl acrylate copolymer, 48 parts of styrene, and 2 parts of glycidyl methacrylate. The production method is the same as in Example 1, except that the ethylene-octene copolymer in the second step is replaced with ethylene-methyl acrylate copolymer (29MA03, SK General Chemical). The low-density polyethylene-styrene graft copolymer is produced from 65 parts of low-density polyethylene and 35 parts of styrene.

[0049] After uniformly mixing the above raw materials, the mixture is fed into an extruder with an L / D ratio of 52:1 and extruded at a processing temperature of 230-260°C and a rotation speed of 500 rpm to obtain a sample. After drying the pellets, test specimens are prepared by injection molding using a conventional method and subjected to testing. (Comparative Example 1)

[0050] The procedure was the same as in Example 1, except that the ethylene-octene-styrene-glycidyl methacrylate graft copolymer was replaced with 5 parts graphite. (Comparative Example 2)

[0051] The procedure was the same as in Example 2, except that the wear-resistant and sound-dampening agent was changed to the same amount of PTFE (L-5, Daikin Industries). (Comparative Example 2')

[0052] The procedure was the same as in Example 2, except that no wear-resistant / sound-dampening agents or wear-resistant additives were added. (Comparative Example 3)

[0053] The procedure was the same as in Example 3, except that a low-density polyethylene-styrene-maleic anhydride graft copolymer was not added as an abrasion-resistant and sound-dampening agent. (Comparative Example 4)

[0054] Except for changing the wear-resistant and sound-dampening agent to the same amount of PTFE (L-5, Daikin Industries), the procedure was the same as in Example 4. (Comparative Example 4')

[0055] The procedure was the same as in Example 4, except that only 4 parts of ethylene-vinyl acetate-styrene-acrylic acid graft copolymer were used as an abrasion-resistant and sound-dampening agent, and no abrasion-resistant additive was added. (Comparative Example 5)

[0056] The procedure was the same as in Example 5, except that ultra-high molecular weight polyethylene-styrene graft copolymer and low-density polyethylene-styrene-glycidyl methacrylate graft copolymer were not added as abrasion-resistant and sound-dampening agents, and were replaced with 10 parts of UHMWPE. (Comparative Example 5')

[0057] The procedure was the same as in Example 5, except that only 10 parts of ultra-high molecular weight polyethylene-styrene graft copolymer was added as an abrasion-resistant and sound-dampening agent. (Comparative Example 6)

[0058] The procedure was the same as in Example 6, except that low-density polyethylene-styrene graft copolymer was not used, and only 5 parts of ethylene-methyl acrylate-styrene-glycidyl methacrylate graft copolymer were added as an abrasion-resistant and sound-dampening agent. (Comparative Example 6')

[0059] The procedure was the same as in Example 6, except that the wear-resistant and sound-dampening agent was replaced with the same amount of PTFE (L-5, Daikin Industries).

[0060] In the above formulation, ingredients and additives whose manufacturers are not listed are commercially available, standard products.

[0061] [Performance Test]

[0062] Tensile strength: Tested in accordance with ISO 527 standard, with a test speed of 50 mm / min.

[0063] Bending strength: Tested in accordance with ISO 178 standard, with a test speed of 2 mm / min.

[0064] Impact strength with Charpy notch: Tested in accordance with ISO 179-1 standard, the impact energy is 4J.

[0065] Friction and wear test: Tested in accordance with GB / T 3960-2016 standard, with a test duration of 2 hours and a load of 196N.

[0066] Stick-Slip Noise (RPN) Test: In accordance with the VDA 230-206 method, the RPN value is measured under different sliding speeds of 1 mm / s and 4 mm / s, and different loads of 10 N and 40 N to evaluate the friction noise of the material. Based on the VDA 230-206 standard, the likelihood of the stick-slip phenomenon occurring in the material is classified into 10 levels. An RPN value of 1-3 indicates a low risk of the material exhibiting stick-slip noise. An RPN value of 4-6 indicates a moderate risk of the material exhibiting stick-slip noise. An RPN value of 7-10 indicates a relatively high probability of the material exhibiting stick-slip noise when subjected to friction.

[0067] The mechanical properties, friction properties, and noise test results of the samples prepared from each example and comparative example are shown in Tables 1 to 6.

[0068] [Table 1]

[0069] [Table 2]

[0070] [Table 3]

[0071] Table 1 shows a performance comparison of glass fiber abrasion-resistant reinforced PPS. The difference between Example 1 and Comparative Example 1 is whether or not ethylene-octene-styrene-glycidyl methacrylate graft copolymer is used as an abrasion-resistant and sound-dampening agent. The results show that, due to the synergistic effect of the GMA functional groups in the ethylene-octene-styrene-glycidyl methacrylate graft copolymer and the toughening and abrasion resistance of POE, there is not only no loss of strength compared to glass fiber reinforced PPS using graphite alone, but the notched impact strength is significantly improved, and more importantly, the abrasion resistance test data comprehensively surpassed the effect of using graphite alone.

[0072] From the data for Example 2, Comparative Example 2, and Comparative Example 2' in Table 2, it can be seen that when 10 parts of linear low-density polyethylene-styrene graft copolymer BP-231, 10 parts of PTFE, and no abrasion-resistant or sound-dampening additives are added to the glass fiber-reinforced PA66 compound, there are no significant differences in the basic mechanical property test data. The notched impact properties of Example 2 are slightly superior, indicating that the linear low-density polyethylene has good toughness and has a certain promoting effect on improving the impact properties of the overall material system. On the other hand, Comparative Example 2', which does not contain abrasion-resistant or sound-dampening additives, has superior tensile and bending properties, but this is mainly due to the high glass fiber content, and it has the lowest impact properties and the worst friction and abrasion test results. When BP-231 is replaced with the same amount of PTFE in Comparative Example 2, not only is there no advantage in mechanical properties, but the abrasion resistance effect is also inferior to that of BP-231. The main reasons for this are that PTFE has no reinforcing effect, has low compatibility with the matrix, and the effect of improving friction properties is limited when the amount added is insufficient. Figure 2 shows the wear mark widths of the friction test specimens for Example 2(a), Comparative Example 2(b), and Comparative Example 2'(c), respectively, and the superiority of the example is very clear.

[0073] Table 3 shows the performance test results of carbon fiber reinforced PA6 for Example 3 and Comparative Example 3. The Example uses a composite of low-density polyethylene-styrene-maleic anhydride graft copolymer and molybdenum disulfide, and its abrasion resistance clearly surpasses that of the Comparative Example which uses molybdenum disulfide alone. Furthermore, the graft copolymer contains reactive maleic anhydride functional groups, which interact with nylon and carbon fibers to improve the bonding strength between the carbon fibers and the nylon matrix. Additionally, the low-density polyethylene in the graft copolymer works in conjunction with the impact modifier to provide a toughening effect.

[0074] [Table 4]

[0075] Table 4 shows the results of applying different abrasion resistance and noise reduction measures to polyacetal. Example 4 and Comparative Example 4 employ a composite measure of ethylene-vinyl acetate-styrene-acrylic acid graft copolymer and UHMWPE, and a composite measure of PTFE and UHMWPE, respectively, and the differences in mechanical property data are not significant. In the example, the introduction of ethylene-vinyl acetate-styrene-acrylic acid with a polyfunctional group structure resulted in slightly superior toughness and slightly better abrasion resistance than the PTFE and UHMWPE composite. More importantly, the composite measure of the example clearly outperformed Comparative Example 4 in noise test results, and the RPN values ​​of Example 4 were all lower than those of Comparative Example 4 under the same test conditions. In Comparative Example 4', no composite measure was used, and only ethylene-vinyl acetate-styrene-acrylic acid graft copolymer was added as an abrasion resistance and noise reduction aid. All mechanical properties except impact strength were inferior to Example 4, and the abrasion resistance and noise reduction test results were slightly lower than those of the composite measure in Example 4.

[0076] [Table 5]

[0077] Table 5 shows a performance comparison of wear-resistant PCs, focusing on whether or not the wear-resistant and noise-dampening agent of the present invention was used in both Example 5 and Comparative Example 5. When the entire amount was changed to UHMWPE in the Comparative Example, processing of the PC became more difficult, the appearance of the manufactured sample was extremely poor, the notched impact properties rapidly deteriorated, and the friction and wear properties became at a general level. On the other hand, when the composite wear-resistant and noise-dampening agent of the present invention was used, not only was the friction effect excellent, but the grafted GMA functional groups interacted with the end groups of the PC to prevent hydrolysis by end sealing and maintain the mechanical properties of the material. In Comparative Example 5', only ultra-high molecular weight polyethylene-styrene graft copolymer without reactive functional groups was used. Although the wear resistance was good, it also affected the impact properties and processability of the PC. Because the wear-resistant and noise-dampening agent containing GMA reactive functional groups was not used, compatibility problems arose with the PC, leading to defects in the appearance and performance of the product, and its practicality was greatly reduced.

[0078] [Table 6]

[0079] Table 6 lists the effects of using different wear-resistant and noise-reducing additives in PC / ABS alloys. From the standpoint of mechanical properties, Example 6 shows superior overall properties (rigidity balance), while Comparative Example 6 uses only ethylene-methyl acrylate-styrene-glycidyl methacrylate graft copolymer as the entirety of the wear-resistant and noise-reducing additive, resulting in the best notched impact properties but only average processability. This is because ethylene-methyl acrylate has a toughening effect, while the GMA content in the graft copolymer is too high, excessively participating in the reaction with PC and causing processing difficulties. Comparative Example 6' uses PTFE as the entirety, resulting in a significant decrease in mechanical properties as well as a poor product appearance. From the standpoint of wear resistance and noise reduction, Example 6 employs a strategy of using multiple wear-resistant additives in combination, resulting in excellent wear resistance and, regardless of the conditions, a low-risk RPN value of less than 3 in terms of noise reduction. In systems using only ethylene-methyl acrylate-styrene-glycidyl methacrylate graft copolymer, abrasion resistance is good, but the sound dampening effect is at an average level, and the RPN value is basically in the medium risk range. Comparative Example 6' not only has poor friction characteristics, but also a relatively high probability of producing stick-slip noise.

[0080] The specific embodiments of the present invention have been described above. The present invention is not limited to the above-described embodiments, and it should be understood that a person skilled in the art may make various modifications or alterations within the scope of the claims without affecting the substantial content of the present invention.

Claims

1. A wear-resistant and sound-dampening engineering plastic composition comprising a thermoplastic resin, a wear-resistant and sound-dampening aid, a wear-resistant aid, and a processing aid, wherein the wear-resistant and sound-dampening aid is at least one selected from the group consisting of a polyolefin-styrene graft copolymer or a polyolefin-styrene graft copolymer modified with a reactive functional group.

2. A wear-resistant and sound-dampening engineering plastic composition according to claim 1, wherein the thermoplastic resin is one or more selected from the group consisting of nylon, polyacetal, polyphenylene sulfide, polycarbonate, or alloys thereof; the composition further comprises a reinforcing filler; the reinforcing filler is one or more selected from the group consisting of glass fiber, carbon fiber, or other inorganic minerals; the processing aid comprises at least one selected from the group consisting of antioxidants, lubricants, antibacterial agents, nucleating agents, antistatic agents, ultraviolet absorbers, colorants, compatibilizers, coupling agents, and impact modifiers; and the wear-resistant aid is one or more selected from the group consisting of UHMWPE, polysiloxane, molybdenum disulfide, graphite, and modified fatty acid esters.

3. An abrasion-resistant and sound-dampening engineering plastic composition according to claim 2, characterized in that the weight ratio of thermoplastic resin, reinforcing filler, abrasion-resistant and sound-dampening aid, abrasion-resistant aid, and processing aid is 100:(0-60):(1-20):(0.1-10):(0.1-20).

4. An abrasion-resistant and sound-dampening engineering plastic composition according to claim 1, wherein the polyolefin-styrene graft copolymer is obtained by grafting a styrene polymer onto a substituted or unsubstituted polyolefin molecular main chain; and the polyolefin-styrene graft copolymer modified with a reactive functional group is a graft copolymer obtained by introducing a reactive functional group into a polyolefin-styrene graft copolymer.

5. An abrasion-resistant and sound-dampening engineering plastic composition according to claim 4, characterized in that the polyolefin-styrene graft copolymer or the polyolefin-styrene graft copolymer modified with a reactive functional group has a weight ratio of 50 to 95% polyolefin.

6. A wear-resistant and sound-dampening engineering plastic composition according to claim 4, wherein the polyolefin is at least one selected from the group consisting of low-density polyethylene, high-density polyethylene, linear low-density polyethylene, ultra-high molecular weight polyethylene, ethylene-α-olefin copolymers such as ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, and ethylene-octene copolymer, ethylene-vinyl acetate copolymer and ethylene-acrylic acid ester copolymer; and the reactive functional group is one or more selected from the group consisting of acrylic acid, methacrylic acid, maleic anhydride, fumaric acid, dibutyl maleate, citric acid, itaconic acid and glycidyl methacrylate group.

7. A method for producing the wear-resistant and sound-dampening engineering plastic composition described in claim 1, characterized in that it is produced from a thermoplastic resin, a reinforcing filler, a wear-resistant and sound-dampening aid, a wear-resistant aid, and a processing aid.

8. Use of the wear-resistant and sound-dampening engineering plastic composition according to claim 1 in the manufacture of wear-resistant materials.

9. A wear-resistant and sound-dampening plastic, characterized in that it is manufactured from the wear-resistant and sound-dampening engineering plastic composition described in claim 1.

10. Use of the wear-resistant and sound-dampening plastic described in claim 9 in the manufacture of polymer wear-resistant products.

Citation Information

Patent Citations

  • Wear-resistant PA composition as well as preparation method and application thereof

    CN116478534A